Optimisation of injection moulding process parameters using taguchi and desirability function - Vivekanandan, Panneerselvam (2020)
A large amount of plastic parts presently produced, makes it imperative to search for an alternative for recycling or making use of these materials, since they are not biodegradable. Injection moulding, one of the most prevalent plastics processing technique facilities these recycled materials to be substituted for virgin material in producing plastic parts. However, the deterioration in mechanical properties of the part made of recycled plastic is the major drawback that limits the usage of recycled plastic. One of the foremost causes is variation in processing parameters. It is of critical importance to effectively control all the influencing processing parameters during the manufacturing process by an appropriate optimisation method. Therefore, the main goal of conducting this research is to primarily investigate the effects of injection moulding parameters on the mechanical properties of plastic part made of recycled plastic and to optimise the identified process parameters. In order to achieve the goal, the significant process parameters is identified with proper research on previous studies. Then, a preliminary experiment is conducted by using the selected significant process parameters from previous researches to identify the process parameters value for the principal experiment. In this research, the principal experiment is conducted using recycled polypropylene by adopting L27 OA. The mechanical properties of the specimens are measured in term of tensile strength and flexural modulus respectively. From the experimental analysis and results, it is shown that the most significant processing parameters affecting the tensile strength are melt temperature, injection time and holding time. The most effective process parameters on flexural modulus are melt temperature, holding time and injection pressure. The optimum process parameters is 180°C of melt temperature, 55MPa injection pressure, 30mm/s injection speed, 8s injection time, 20MPa holding pressure, 3s holding time and 25s cooling time. These parameters have optimise the part quality to 199 kgf/cm2 of tensile strength and can result in flexural modulus of 10005 kgf/cm2. This proves that recycled materials are potentially substituted for virgin material. Therefore, the demand for natural resources and energy consumption due to virgin material production can be reduced and environmental problems due to plastics disposal can be diminished as well. Further in future, more responses on mechanical properties of material such as impact strength and compressive strength should be investigated to obtain even better properties of recycled PP.